‘It was a joint plan we worked out together’. How the I-WOTCH programme enabled people with chronic non-malignant pain to taper their opioids: a process evaluation - Martin Underwood; Kate Seers; Charles Abraham; Harbinder Kaur Sandhu; Vivien P Nichols; Sam Eldabe; Alleyne Sharisse; Balasubramanian Shyam; Betteley Lauren; Booth Katie; Carnes Dawn; D Furlan Andrea; et al. (BMJ Open)
Background The Improving the Wellbeing of people with Opioid Treated CHronic pain (I-WOTCH) randomised controlled trial found that a group-based educational intervention to support people using strong opioids for chronic non-malignant pain helped a significant proportion of people to stop or decrease opioid use with no increase in pain-related disability. We report a linked process evaluation of the group-based intervention evaluated in comparison to a usual-care control group that received a self-help booklet and relaxation CD.Methods We interviewed 18 intervention facilitators, and 20 intervention and 20 control participants who had chronic non-malignant pain and were recruited from general (family) practices in the UK. Quantitative data included change mechanism questions on the trial questionnaires which explored motivation, expectations and self-efficacy. Fidelity was assessed by listening to a sample of audio-recorded group sessions and nurse consultations. Quantitative and qualitative data were integrated using ‘follow a thread’ and a mixed-methods matrix.Findings Four overarching themes emerged: (1) the right time to taper, (2) the backdrop of a life with chronic pain, (3) needing support and (4) the benefits of being in a group. Delivery fidelity was good, adherence (83%) and competence (79%) across a range of intervention groups. Staff delivering the intervention found three typical responses to the intervention: resistance, open to trying and feeling it was not the right time. The group experience was important to those in the intervention arm. It provided people with a forum in which to learn about the current thinking about opioid usage and its effects. It also gave them examples of how feasible or personally relevant coming off opioids might be.Conclusion The process evaluation data showed that the I-WOTCH intervention was well delivered, well received and useful for most interviewees. Being ‘the right time’ to taper and having support throughout tapering, emerged as important factors within the context of living with chronic pain.Trial registration number ISRCTN49470934.